Early mortality critically impedes improvements in thyroid cancer survival through a half century - Tichanek, Filip; Försti, Asta; Liska, Vaclv; Hemminki, Otto; Koskinen, Anni; Hemminki, Akseli; Hemminki, Kari (European journal of endocrinology, 2023)
OBJECTIVES: We analyze survival in thyroid cancer from Denmark (DK), Finland (FI), Norway (NO), and Sweden (SE) over a 50-year period (1971-2020), and additionally consider concomitant changes in incidence and mortality. DESIGN: Population-based survival study. METHODS: Relative 1-, 5/1 (conditional)-, and 5-year survival data were obtained from the NORDCAN database for years 1971-2020. Incidence and mortality rates were also assessed. RESULTS: A novel consistent observation was that 1-year survival was worse than 5/1-year survival but the difference between these decreased with time. Relative 1-year survival in thyroid cancer (mean for the 4 countries) reached 92.7% for men and 95.6% for women; 5-year survival reached 88.0% for men and 93.7% for women. Survival increased most for DK which started at a low level and reached the best survival at the end. Male and female incidence rates for thyroid cancer increased 3- and 4-fold, respectively. In the same time, mortality halved for men and for women, it decreased by 2/3. CONCLUSIONS: We documented worse relative survival in the first year than in the 4 subsequent years, most likely because of rare anaplastic cancer. Overall survival in thyroid cancer patients increased in the Nordic countries in the course of 50 years; 5-year survival was close to 90% for men and close to 95% for women. Even though overdiagnosis may explain some of 5-year survival increase, it is unlikely to influence the substantial increase in 1-year survival. The unmet need is to increase 1-year survival by diagnosing and treating aggressive tumors before metastatic spread.
Keywords: treatment; diagnostics; Norway; Thyroid Neoplasms; Norsko; databáze faktografické; Finsko; Male; nádory štítné žlázy; Finland; lidé; Female; mužské pohlaví; ženské pohlaví; anaplastic cancer; relative survival; Humans; Databases, Factual